A Triple Band Polarization Insensitive Graphene-Based Metasurface Absorber in Terahertz Gap - Verma A.S.; Bhattacharyya S. (My University, 2025)
This paper proposes a graphene-based metasurface absorber structure for low, mid, and trailing ranges of terahertz (THz) gap. The unit cell of the structure consists of a patterned graphene layer with simultaneous plus-shaped and swastika-shaped slots grown over a layer of amorphous silicon dioxide (SiO2) backed by a golden layer. The proposed structure offers three absorption bands having bandwidths of 0.83 THz, 0.96 THz and 0.48 THz with respective peaks at 3.03 THz, 6.06 THz, and 9.93 THz. The four-fold symmetry of the unit cell makes the structure polarization insensitive in nature. The structure offers angular stability for oblique incidents up to 40 degrees for both TE and TM modes of polarization. The structure is as thin as ~λ/14 concerning the frequency of first peak absorption, and the periodicity of the unit cell is ~λ/16.5 supporting effective homogeneity condition. The structure can be used for future implementable aspects that can apply to sensing, 6G communications and other biomedical applications. © 2024 IEEE.